BEM analysis of multilayer thin structures using a composite transformation method for boundary integrals. (1st January 2022) - Zhong, Yudong; Hou, Junjian; Feng, Shizhe; Xie, Guizhong; Wang, Xinsheng; He, Wenbin; Wang, Liangwen; Chen, Zhiqiang; Hao, Hongwei
Abstract: In this paper, a composite transformation method is developed to evaluate the singular and nearly singular boundary integrals in the boundary element analysis for multilayer thin structures. The composite transformation method is implemented as follows: Firstly, a sinh transformation method is developed to eliminate the influence of nearly singular integrals in the multilayer thin-structural problem; and then a complex transformation method is improved to deal with the weakly singular integrals. The complex transformation formulations of weakly singular integrals are derived from the composition of the ( α, β ) coordinate transformation and the sinh transformation in β direction. With this method for weakly singular integrals, the weak singularity in the radial direction and the potentially near singularity in the circumferential direction can be removed. Finally, the proposed transformation formulations of singular and nearly singular integrals are used to analyze multi-domain elasticity problem for multilayer thin structures. The numerical results for several examples are presented to demonstrate the computational accuracy of the proposed method.